Proceedings of the XV Ibero-American Congress of Mechanical Engineering CIBIM 22 / CIBEM 22 - Vizán Idoipe, Antonio; García Prada, Juan Carlos (Springer Nature, 2023)
This open access book shows some of the highlights presented at the XV Ibero-American Congress of Mechanical Engineering. The papers explore the forefront of Mechanical Engineering, containing research into fluid mechanics, energy systems, tribology, materials science, robotics, mechatronics, biomechanics, instrumentation, thermodynamics, and mechanical sustainability.